A Review of New High-Throughput Methods Designed for Fluorescence Lifetime Sensing From Cells and Tissues - Bitton, Aric; Sambrano, Jesus; Valentino, Samantha; Houston, Jessica P. (Frontiers in Physics, 2021)
Though much of the interest in fluorescence in the past has been on measuring spectral qualities such as wavelength and intensity, there are two other highly useful intrinsic properties of fluorescence: lifetime (or decay) and anisotropy (or polarization). Each has their own set of unique advantages, limitations, and challenges in detection when it comes to use in biological studies. This review will focus on the property of fluorescence lifetime, providing a brief background on instrumentation and theory, and examine the recent advancements and applications of measuring lifetime in the fields of high throughput fluorescence lifetime imaging microscopy (HT-FLIM) and time-resolved flow cytometry (TRFC). In addition, the cross-over of these two methods and their outlook will be discussed.